The effect of soy protein containing soy isoflavones on serum concentration of cell adhesion molecules: A systematic review and meta-analysis of randomized controlled trials - Mitra Hariri; Hamid Reza Baradaran; Ali Gholami (Elsevier, 2021)
Background: Soy protein in combination with soy isoflavones might reduce the serum concentration of inflammatory mediators. In this study, we attempted to summarize the effect of soy protein combined with soy isoflavones on circulating E-selectin, intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) in adults. Methods: Clinicaltrials.gov, Web of Science, Cochrane Library, PubMed, and Scopus were searched for English articles with no time limit regarding publication up to December 2020. Thereafter, the mean changes from baseline and their standard deviations (SDs) for both intervention and comparison groups were used to calculate the effect size. We used DerSimonian and Laird random-effects model if the heterogeneity test was statistically significant. Cochran's Q test and I-squared statistic were also used to calculate the statistical heterogeneity of the intervention effects. Results: Eight articles were found as eligible for this study. The treatment duration was between 6 and 24 weeks. Soy isoflavones dose was in a range of 30-112 mg/day and soy protein dose was in a range of 11.25-52 g/day. Overall, taking soy protein supplements containing soy isoflavones was not associated with changes in cell adhesion molecules, E-selectin, ICAM-1, or VCAM-1 (WMD = 0.65, 95 % CI: -2.58, 3.89; p = 0.692; WMD = 2.68, 95 % CI: -0.98, 6.34; p = 0.151; WMD = 2.66, 95 % CI: -6.28, 11.61; p = 0.559, respectively). Conclusion: The combination of soy protein and soy isoflavones was not significantly associated with changes in levels of E-selectin, ICAM-1, and VCAM-1. However, we need more studies with a large sample size and more participants with different age categories in this regard.